Flow control in iOS - Hernández-Castro, Franklin (2012)
This paper explain the control flows that are used by programming applications in iOS, trying to summarize the most important aspects to be considered by programming mobile devices like iPhone and iPad. Because iOS environment, is strictly a object-oriented one(OOP), control flows are not obvious, besides Apple® use design patterns highly recommended in this type of programming. Here we introduces some of them.